Pengaruh Kualitas Produk dan Persepsi Harga Terhadap Keputusan Pembelian Produk Pakaian Thrifting di Pasar Senen - Magdalena Liessantri Ndraha; Ir. Budi Santosa Kramadibrata (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The fashion industry continues to grow rapidly, creating new trends that influence people's lifestyles. The thrifting phenomenon at Pasar Senen has become a popular shopping alternative due to its affordable prices and product quality. This study aims to analyze the influence of product quality and price perception on purchasing decisions for thrifted clothing. The research employs an associative quantitative approach involving 96 respondents. The research instrument is a questionnaire tested for validity and reliability. Data analysis includes descriptive and correlation analysis, while hypothesis testing uses multiple linear regression analysis. The results indicate a positive influence of product quality and price perception on purchasing decisions, with an R-Square value of 0.805. The study's limitation lies in its scope, which focuses only on one market and does not consider other variables or moderators that may impact purchasing decisions more broadly.